An overview of protein N-glycosylation diversity in microalgae - van Bockstaele-Fuentes, Julia; Mati-Baouche, Narimane; Lupette, Josselin; Gargouch, Nesrine; Rivet, Elodie; Lerouge, Patrice; Bardor, Muriel (Frontiers in Plant Science, 2025)
Microalgae are unicellular photosynthetic eukaryotic organisms that arose from distinct endosymbiotic events yielding a wide phylogenetic diversity. In contrast, a single lineage of green algae charophytes gives rise to all land plants. A large number of N-glycan structures were already characterized but the study of glycans N-linked to proteins in these unicellular organisms only recently begun and concerns a limited number of species. These structures differ to a large extent from known structures and exhibit various glycan decorations not reported so far in land plants. However, many pieces of the puzzle are still missing for a full understanding of the protein N-glycosylation biosynthesis in microalgae despite the structural elucidation of lipid-linked oligosaccharide precursors and the biochemical characterization of some Golgi glycosyltransferases. In the present review, we will give an overview of the recently published data on protein N-glycosylation in microalgae which enable to draw an updated picture of this sophisticated cellular process leading to a huge diversity of N-glycan structures. In this work, we will also highlight the arabinosylation and xylosylation of N-glycans in plants and microalgae.